Multiple active passive tuned mass dampers for structures under the ground acceleration. - Li, Chunxiang (Earthquake engineering & structural dynamics.)
Multiple active passive tuned mass dampers (MAPTMD) consisting of many active passive tuned mass dampers (APTMDs) with a uniform distribution of natural frequencies have been, for the first time here, proposed for attenuating undesirable oscillations of structures under the ground acceleration. The MAPTMD is manufactured by keeping the stiffness and damping coefficient constant and varying the mass. The control forces in the MAPTMD are generated through keeping the identical displacement and velocity feedback gain and varying the acceleration feedback gain. The structure is represented by the mode generalized system corresponding to the specific vibration mode that needs to be controlled. Through minimization of the minimum values of the maximum dynamic magnification factors (DMF) of the structure with the MAPTMD (i.e. through implementation of Min.Min.Max.DMF), the optimum parameters of the MAPTMD are investigated to delineate the influence of the important parameters such as mass ratio, total number, normalized acceleration feedback gain coefficient and system parameter ratio on the effectiveness (i.e. Min.Min.Max.DMF) and robustness of the MAPTMD. The optimum parameters of the MAPTMD include the optimum frequency spacing, average damping ratio and tuning frequency ratio. Additionally, for the sake of comparison, the results for a single APTMD are also taken to significantly reduce the oscillations of structures under the ground acceleration. Also, it is shown that the MAPTMD can render high robustness and has better effectiveness than a single APTMD. In particularly, if and when requiring a large active control force, MAPTMD is more promising for practical implementations on seismically excited structures with respect to single APTMD.